Increased burned area in the Pantanal over the past two decades - Correa, Danielle Blazys (2022)
Wildfires are behaving differently now if compared to other time in history in relation to frequency, intensity and affected ecosystems. In Brazil, unprecedent fires are being experienced in the last 10 years and to prevent and minimize similar disasters we must understand more about the natural and human influences on fires on each ecosystem as well as the gaps to fire combat strategies. The Brazilian Pantanal is the largest contiguous wetland in the world and a complex environmental system. In 2020 Pantanal experienced a catastrophic wildfire which burned out of control that shocked the world. The fire in Pantanal is expected to escalate given the increase in drought episodes, inadequate fire management strategies and weak environment regulations. In this study, we analyzed recent patterns and changes in fire frequency across the Pantanal based on land use and cover classes. The inter-annual variability of the fire and land cover changes between 2000 and 2021 was assessed using burned area (BA) from MCD64A1 V.6 product and land use and land cover (LULC) data from Landsat imagery. Our results showed that while smaller BA were more frequent for all LULC, forest and grassland classes represented much larger BA with lower frequencies. Cropland showed the smallest burned area among the LULC. Given the differences in the rates of recovery and regeneration after fire for different classes, Pantanal should be systematically monitored to develop a more effective fire combat strategy. We understand that our work demonstrates fundamental spatiotemporal clues to managers to strategically approach unusual fires with result of what periods were exceptional burned according to LULC classes, as observed for Forests in 2020 and an exponential burning growth in cropland during late dry (LD) season since 2014.